2010
DOI: 10.1186/1475-2875-9-197
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of innate defences against Plasmodium falciparum in immunodeficient mice

Abstract: BackgroundMice with genetic deficiencies in adaptive immunity are used for the grafting of human cells or pathogens, to study human diseases, however, the innate immune responses to xenografts in these mice has received little attention. Using the NOD/SCID Plasmodium falciparum mouse model an analysis of innate defences responsible for the substantial control of P. falciparum which remains in such mice, was performed.MethodsNOD/SCID mice undergoing an immunomodulatory protocol that includes, clodronate-loaded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 50 publications
6
40
0
Order By: Relevance
“…To address this idea directly, we depleted granulocytes from both strains by administering anti-Ly6-G antibodies, which have previously been shown to selectively deplete granulocytes in vivo (36). Flow analysis confirmed that after antibody depletion, granulocyte numbers were reduced to below detection levels in both strains (Supplemental Figure 4).…”
Section: Figurementioning
confidence: 81%
“…To address this idea directly, we depleted granulocytes from both strains by administering anti-Ly6-G antibodies, which have previously been shown to selectively deplete granulocytes in vivo (36). Flow analysis confirmed that after antibody depletion, granulocyte numbers were reduced to below detection levels in both strains (Supplemental Figure 4).…”
Section: Figurementioning
confidence: 81%
“…Additionally, NSG mice shown lesser effect of aging which was due to the minimalized effect by interposition impact rendered by the IL-2Rγ mutation, along with a small sample size exhibiting marginal benefit of aging in the said mouse strain. The NSG-IV murine model when transplanted with human cells showed a great complementation of IL-2Rγ mutation byclo-lip treatment in controlling inflammation mounted by the cell engraftment which reportedly showed the reduction in the erythrophagocytosis [1,2,[4][5][6][7].…”
Section: Mutation In (Il-2r) γ-Chainmentioning
confidence: 99%
“…which is highly evolved and a complex organism. The mercurial behavior of parasite because of the secretion of tens of thousands of proteins [4,5,48]. A) Upper panel shows significant human blood chimerism in NSG mice over the period of more than 21 days, and B) lower panel illustrates the sizeable parasitemia using three (PAM, 3D7 and K1) P. falciparum strains in the huRBC reconstituted NSG mice.…”
Section: The Malaria Vaccine Development: a Challenging Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting new IV model based on NSG mice presents several advantages over previously available models. It offers greater reproducibility, with 100% of mice successfully grafted without the need for mouse-adapted parasites, consistent curves of parasitemia, and high levels of infection with up to 40-50% of total erythrocytes infected (Arnold et al, 2010).…”
mentioning
confidence: 99%